Reinforced polyamide composite material as well as preparation method and application thereof

By adding a composite wear-resistant agent of high molecular weight polyethylene and polyethylene glycol to the polyamide composite material, the problem of insufficient humidity and heat resistance and wear resistance in high temperature and high humidity environments is solved, and the problem of insufficient humidity resistance and wear resistance of polyamide composite material is achieved. The material maintains good performance in high temperature and high humidity environments.

CN119463471AActive Publication Date: 2025-02-18TIANJIN KINGFA NEW MATERIAL +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411536187.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-18
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

Polyamide composites have problems with insufficient aging resistance and wear resistance in high temperature and high humidity environments.

Method used

By adding a composite wear-resistant agent of high molecular weight polyethylene and polyethylene glycol of a specific ratio to the polyamide composite material, the hydroxyl group of polyethylene glycol is used to improve the activity of the high molecular weight polyethylene surface, and with polyamide and glass The fibers form a stable interface structure.

Benefits of technology

The wear resistance and humidity and heat aging resistance of polyamide composite materials are significantly improved, so that the material can still maintain good performance in high temperature and high humidity environments.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The reinforced polyamide composite material comprises the following components in parts by weight: 40-50 parts of polyamide; 40 to 70 parts of glass fiber; 7-15 parts of a compound wear-resistant agent; the compound wear-resistant agent is a compound of high molecular weight polyethylene and polyethylene glycol. Through compounding of high-molecular-weight polyethylene and polyethylene glycol, hydroxyl groups of polyethylene glycol can effectively improve the surface activity of high-molecular-weight polyethylene during melt blending modification, and the high-molecular-weight polyethylene, polyamide and the whole material system form a stable interface structure, so that the material is effectively prevented from being influenced by an external high-temperature and high-humidity environment; therefore, the material can maintain good mechanical properties in a high-temperature and high-humidity environment, and the wear resistance can be further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a reinforced polyamide composite material and a preparation method and application thereof. Background Art

[0002] Polyamide is widely used as an engineering material in various fields. With the continuous improvement of technology, the product types are increasing. However, with the development of modern high technology, the products with durability, friction resistance and complex structural design are gradually increasing, which puts higher requirements on the comprehensive performance of materials.

[0003] However, due to the water absorption of polyamide composite materials, the resistance to wet heat aging needs to be improved. At the same time, the wear resistance also needs to be improved.

[0004] CN112552676A records a polyamide composite material that can be gas-assisted molded, including 37-86.7% polyamide resin, 10-40% flat glass fiber, 2-8% impact modifier, 0.5-5% ultra-high molecular weight polyethylene, 0.2-2% polyethylene glycol, 0.1-3% colorant, and 0.5-5% additive. This solution mainly utilizes polyethylene glycol to form intermolecular hydrogen bonds with polyamide, reduces the crystallization temperature of the composite material, improves the appearance, and the flat glass fiber helps to provide a more isotropic dispersion, which improves the fluidity of the composite material. However, this solution is limited in improving heat and moisture resistance and wear resistance. Summary of the invention

[0005] The purpose of the present invention is to overcome the above technical defects and provide a high temperature, moisture and wear resistant reinforced polyamide composite material, as well as a preparation method and application.

[0006] The present invention is achieved through the following technical solutions: A reinforced polyamide composite material, comprising the following components by weight percentage: Polyamide 40-50 parts; Glass fiber 40-70 parts; Compound anti-wear agent 7-15 parts; The compound wear-resistant agent is a compound of high molecular weight polyethylene and polyethylene glycol, and the weight ratio of high molecular weight polyethylene to polyethylene glycol is (0.79-1.8):1; The viscosity average molecular weight of the high molecular weight polyethylene is 800,000-2.1 million; The weight average molecular weight of the polyethylene glycol is 900-13000.

[0007] The content of polyamide that can achieve the purpose of the present invention can be 40 parts, 42 parts, 44 parts, 46 parts, 48 ​​parts, 50 parts. The content of glass fiber can be 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, etc. The content of compound wear-resistant agent can be 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, etc.

[0008] The weight ratio of high molecular weight polyethylene:polyethylene glycol can be 0.79:1, 0.85:1, 0.9:1, 1.0:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, etc.

[0009] The viscosity-average molecular weight of high molecular weight polyethylene can be 800,000, 900,000, 1,000,000, 1,100,000, 1,200,000, 1,300,000, 1,400,000, 1,500,000, 1,600,000, 1,700,000, 1,800,000, 1,900,000, 2,000,000, 2,100,000, etc.

[0010] The weight average molecular weight of polyethylene glycol can be 900, 1000, 2000, 3000, 4000, 5000, 6000, 7000, 8000, 9000, 10000, 11000, 12000, 13000, etc.

[0011] In the technical solution of the present invention, the polyamide accounts for no less than 30wt% of the total weight of the reinforced polyamide composite material.

[0012] In the present invention, the content of high molecular weight polyethylene is in the range of 3.1-9.8 parts, and the content of polyethylene glycol is in the range of 2.4-8.3 parts.

[0013] The content of high molecular weight polyethylene can be 3.1 parts, 3.5 parts, 4.0 parts, 4.5 parts, 5.0 parts, 5.5 parts, 6.0 parts, 6.5 parts, 7.0 parts, 7.5 parts, 8.0 parts, 8.5 parts, 9.0 parts, 9.8 parts, etc. The content of polyethylene glycol can be 2.4 parts, 3.0 parts, 3.5 parts, 4.0 parts, 4.5 parts, 5.0 parts, 5.5 parts, 6.0 parts, 6.5 parts, 7.0 parts, 7.5 parts, 8.0 parts, 8.3 parts, etc.

[0014] Preferably, the weight ratio of high molecular weight polyethylene:polyethylene glycol is (1.1-1.5):1.

[0015] Preferably, the viscosity average molecular weight of the high molecular weight polyethylene is 1.5 million to 2 million.

[0016] Preferably, the weight average molecular weight of the polyethylene glycol is 3000-9000.

[0017] The test method for viscosity average molecular weight of polyethylene is: GB / T1632.3-2010.

[0018] The weight average molecular weight test method of polyethylene glycol is as follows: weigh appropriate amount of polyethylene glycol 600, polyethylene glycol 1000, polyethylene glycol 4000, polyethylene glycol 7000, polyethylene glycol 10000 molecular weight reference substances, dissolve and dilute with mobile phase to make a solution containing about 2 mg per 1 ml as reference substance solution. Weigh appropriate amount of sample, dissolve and dilute with mobile phase to make a solution containing about 2 mg per 1 ml as test solution. Determine according to molecular exclusion chromatography (General Rule 0514), use gel chromatography column with appropriate separation range, 0.1 mol / L sodium nitrate solution (containing 0.02% antibacterial agent) as mobile phase, differential refractive index detector; detector temperature 35°C, column temperature 35°C, take 100 μl of reference substance solution and inject it into liquid chromatograph, record chromatogram, calculate regression equation by GPC software, linear correlation coefficient R should not be less than 0.99. Take 100μl of the test solution and measure it in the same way. Calculate the weight average molecular weight and molecular weight distribution of the test sample according to the regression equation. The weight average molecular weight of the test sample should be 90%-110% of the labeled value, and the distribution coefficient should be 90%-110% of the product labeled value. The antibacterial agent is 2-methyl-4-isothiazoline-3-one and 5-chloro-2-methyl-4-isothiazoline-3-one (such as ProClin300) or other small molecule antibacterial agents with equivalent antibacterial efficacy.

[0019] The polyamide resin is selected from at least one of aliphatic polyamide resin, semi-aromatic polyamide resin and polylactamide resin.

[0020] The aliphatic polyamide resin is selected from PA66, PA46, PA610, PA612, PA56, PA510, PA512, PA910, PA912, PA913, PA914, PA915, PA616, PA936, PA1010, PA1012, PA1013, PA1014, PA1210, PA1212, PA1213, PA1214, PA614, PA613, PA615, PA616 and the like.

[0021] The semi-aromatic polyamide is selected from PA MXD6, PA10T, PA10T1010, PA10T66, PA6T, PA6T66, PA9T and the like.

[0022] The polylactam is selected from PA5, PA6, PA11, PA12 and the like.

[0023] By weight percentage, the invention further comprises 0-5 parts of an auxiliary agent, wherein the auxiliary agent is selected from at least one of a lubricant, a nucleating agent and an antistatic agent.

[0024] The preparation method of the reinforced polyamide composite material of the present invention comprises the following steps: uniformly mixing polyamide and a wear-resistant agent according to a ratio, feeding into a twin-screw extruder for melt mixing, feeding glass fiber side material, and extruding granulation to obtain the reinforced polyamide composite material; wherein the screw length-diameter ratio of the twin-screw extruder is 40-48:1, the screw barrel temperature is 230-260°C, and the screw speed is 200-550rpm.

[0025] The reinforced polyamide composite material of the present invention is used for preparing electrical appliance housings and high temperature and high humidity resistant and wear resistant parts in the new energy field.

[0026] The present invention has the following beneficial effects: The present invention adds high molecular weight polyethylene and polyethylene glycol in a specific ratio into the reinforced polyamide composite material. During melt blending and modification, the hydroxyl group of the polyethylene glycol can effectively improve the activity of the surface of the high molecular weight polyethylene, form a stable interface structure with the polyamide and the glass fiber, effectively protect the material from the influence of the external high temperature and high humidity environment, and significantly improve the wear resistance, so that the material can maintain a good performance retention rate after being in a high temperature and high humidity environment. DETAILED DESCRIPTION

[0027] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0028] The sources of raw materials used in the present invention are as follows: PA66: PA66 EPR27, Shenma Group; PA6: PA6 HY-2800A, marine chemical fiber; PA10T: VICNYL 6100P, Zhuhai Wantong Special Engineering Plastics Co., Ltd. PA1010: PA1010 G150, Shandong Guangyin New Materials Co., Ltd.; High molecular weight polyethylene A: viscosity average molecular weight about 1.2 million, PE-UHMW I-2, Sinopec; High molecular weight polyethylene B: viscosity average molecular weight about 1.57 million, PE-UHMW MI, Sinopec; High molecular weight polyethylene C: viscosity average molecular weight about 400,000, GUR 2105, Celanese; High molecular weight polyethylene D: viscosity average molecular weight about 6.7 million, GUR 4130, Celanese; Polyethylene glycol A: weight average molecular weight 1000, PEG-1000, Shanghai Haoyuan Biopharmaceutical Technology Co., Ltd.; Polyethylene glycol B: weight average molecular weight 4000, PEG-4000, Shanghai Haoyuan Biopharmaceutical Technology Co., Ltd.; Polyethylene glycol C: weight average molecular weight 8000, PEG-8000, Shanghai Haoyuan Biopharmaceutical Technology Co., Ltd.; Polyethylene glycol D: weight average molecular weight 10000, PEG-10000, Shanghai Haoyuan Biopharmaceutical Technology Co., Ltd.; Polyethylene glycol E: weight average molecular weight 500, PEG-500, Shanghai Haoyuan Biopharmaceutical Technology Co., Ltd.; Polyethylene glycol F: weight average molecular weight 15000, PEG-15000, Shanghai Haoyuan Biopharmaceutical Technology Co., Ltd.; Glass fiber: ECS10-3.0-T435N, Taishan Group.

[0029] Embodiment and comparative example The preparation method of the reinforced polyamide composite material: polyamide and wear-resistant agent are mixed uniformly according to the ratio, put into a twin-screw extruder for melt mixing, glass fiber side feeding, and extrusion granulation to obtain a reinforced polyamide composite material; wherein the screw aspect ratio of the twin-screw extruder is 44:1, the barrel temperature is 230~260℃, and the screw speed is 350rpm.

[0030] Various test methods: (1) Abrasion resistance: The test was conducted on a color fastness wear tester, with a weight of 226 N applied, using 80-mesh coarse sandpaper as the grinding surface, and the test was conducted at a frequency of 1 time / s, with a cycle mileage of 100 mm and 5,000 cycles. The wear rate of the test sample was measured. The wear rate test method is as follows: Wear rate = (sample weight before test - sample weight after test) / sample weight before test * 100%.

[0031] (2) Resistance to heat and humidity aging: Heat and humidity aging test was conducted at a temperature of 60 degrees and a humidity of 85% for 200 hours. The tensile strength retention of the material before and after the test was compared according to ISO 527 standard.

[0032] The specific calculation formula is as follows: Performance retention rate = (tensile strength after wet heat test / tensile strength before wet heat test) / 100%.

[0033] Table 1: Contents of components (parts by weight) and test results of reinforced polyamide composite materials of Examples 1-7 Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 PA66 45 45 45 45 PA6 40 PA10T 45 PA1010 50 Fiberglass 50 40 60 70 50 50 50 High molecular weight polyethylene A 6.3 3.7 5.3 7.9 5.3 7.2 7.7 Polyethylene glycol A 5.7 3.3 4.7 7.1 6.7 4.8 4.3 Polyethylene: Polyethylene glycol weight ratio 1.1 1.1 1.1 1.1 0.8 1.5 1.8 Wear rate / % 1.5 1.7 1.6 2.1 1.7 1.6 1.9 Performance retention rate / % 85 84 85 80 82 87 80 It can be seen from Examples 1 / 5 / 6 / 7 that the preferred weight ratio of high molecular weight polyethylene:polyethylene glycol is (1.1-1.5):1, which has the highest abrasion resistance and tensile strength retention rate after wet heat aging.

[0034] Table 2: Content of each component (parts by weight) and test results of reinforced polyamide composite materials of Examples 8-11 Example 8 Example 9 Example 10 Embodiment 11 PA66 45 45 45 45 Fiberglass 50 50 50 50 High molecular weight polyethylene A 6.3 6.3 6.3 High molecular weight polyethylene B 6.3 Polyethylene glycol A 5.7 Polyethylene glycol B 5.7 Polyethylene glycol C 5.7 Polyethylene glycol D 5.7 Polyethylene: Polyethylene glycol weight ratio 1.1 1.1 1.1 1.1 Wear rate / % 1.4 1.6 1.4 1.9 Retention rate of heat and humidity aging resistance / % 87 86 85 80 It can be seen from Examples 1 / 8 that the viscosity average molecular weight of the high molecular weight polyethylene is preferably 1.5 million to 2 million.

[0035] It can be seen from Examples 1 / 9 / 10 / 11 that the preferred weight average molecular weight range of polyethylene glycol is 3000-9000.

[0036] It can be seen from the above examples that the wear rate of the reinforced polyamide composite material of the present invention is less than 2%, and the tensile strength performance retention rate after moisture-heat aging is ≥80%.

[0037] Table 3: Content of each component (parts by weight) and test results of comparative reinforced polyamide composite materials Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 PA66 45 45 45 45 45 45 Fiberglass 50 50 50 50 50 50 High molecular weight polyethylene A 6.3 6.3 3 8 High molecular weight polyethylene C 6.3 High molecular weight polyethylene D 6.3 Polyethylene glycol A 5.7 5.7 9 4 Polyethylene glycol E 5.7 Polyethylene glycol F 5.7 Polyethylene: Polyethylene glycol weight ratio 1.1 1.1 1.1 1.1 0.3 2 Wear rate / % 4.3 2.2 6.8 5.7 4.0 3.4 Performance retention rate / % 73 55 60 58 53 49 It can be seen from Comparative Example 1 that when the viscosity-average molecular weight of the high molecular weight polyethylene is too low, the wear resistance is significantly reduced, and the resistance to wet heat aging is significantly reduced.

[0038] It can be seen from Comparative Example 2 that when the viscosity-average molecular weight of the high molecular weight polyethylene is too high, it is easy to crosslink during the melt processing, resulting in a slight decrease in wear resistance, especially a significant decrease in moisture and heat aging resistance.

[0039] It can be seen from comparative examples 3 / 4 that when the weight average molecular weight of polyethylene glycol is too high or too low, the wear resistance and the resistance to wet heat aging are simultaneously reduced.

[0040] It can be seen from Comparative Examples 5 / 6 that if the ratio of high molecular weight polyethylene / polyethylene glycol is not within the scope of the present invention, the wear resistance and resistance to wet heat aging are poor.

Claims

1. A reinforced polyamide composite material, characterized in that: By weight, it includes the following components: Polyamide 40-50 parts; Glass fiber 40-70 parts; Compound anti-wear agent 7-15 parts; The compound wear-resistant agent is a compound of high molecular weight polyethylene and polyethylene glycol, and the weight ratio of high molecular weight polyethylene to polyethylene glycol is (0.79-1.8):1; The viscosity average molecular weight of the high molecular weight polyethylene is 800,000-2.1 million; The weight average molecular weight of the polyethylene glycol is 900-13000.

2. The reinforced polyamide composite material according to claim 1, characterized in that: The weight ratio of high molecular weight polyethylene: polyethylene glycol is (1.1-1.5):

1.

3. The reinforced polyamide composite material according to claim 1, characterized in that: The viscosity average molecular weight of the high molecular weight polyethylene is 1.5 million to 2 million.

4. The reinforced polyamide composite material according to claim 1, characterized in that: The weight average molecular weight of the polyethylene glycol is 3000-9000.

5. The reinforced polyamide composite material according to claim 1, characterized in that: The polyamide resin is selected from at least one of aliphatic polyamide resin, semi-aromatic polyamide resin and polylactamide resin.

6. The reinforced polyamide composite material according to claim 1, characterized in that: By weight percentage, the invention further comprises 0-5 parts of an auxiliary agent, wherein the auxiliary agent is selected from at least one of a lubricant, a nucleating agent and an antistatic agent.

7. The method for preparing the reinforced polyamide composite material according to any one of claims 1 to 6, characterized in that: The following steps are involved: The polyamide and the wear-resistant agent are uniformly mixed according to a ratio, put into a twin-screw extruder for melt mixing, glass fiber side feeding, and extrusion granulation to obtain a reinforced polyamide composite material; wherein the twin-screw extruder has a screw length-diameter ratio of 40-48:1, a screw barrel temperature of 230-260°C, and a screw speed of 200-550rpm.

8. Use of the reinforced polyamide composite material according to any one of claims 1 to 6, characterized in that: Used to prepare electrical appliance casings and high temperature and high humidity resistant parts in the new energy field.

Citation Information

Patent Citations

  • Polyamide composite material capable of being subjected to gas-assisted molding

    CN112552676A

  • Resin composite material and its preparation method and use

    CN102952327A

  • Polyether-b-polyamide (PEBA) / polyethyleneglycol (PEG) or polyoxyethylene (PEO) blend membrane, and preparation and application thereof

    CN103100313A

  • Anti-pollution polyamide composite membrane and preparation method thereof

    CN104437111A